Level of knowledge of mothers with children aged 3 to 6 years about cariogenic diet habits - Alisson Julieth Yaguana-Loor; Jaime Fernando Armijos-Moreta; Silvia Marisol Gavilanez-Villamarín (Revista Información Científica, 2022)
Introduction: good oral health has an essential impact throughout the human life cycle. The correct eating habits have proven to be effective on good oral health, where cariogenic diet is of fundamental interest.